2015
DOI: 10.1093/cercor/bhv281
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Alterations in Infants at Risk for Developmental Dyslexia

Abstract: Developmental dyslexia (DD) is a heritable condition characterized by persistent difficulties in learning to read. White matter alterations in left-lateralized language areas, particularly in the arcuate fasciculus (AF), have been observed in DD, and diffusion properties within the AF correlate with (pre-)reading skills as early as kindergarten. However, it is unclear how early these alterations can be observed. We investigated white matter structure in 14 infants with (FHD+; ages 6.6-17.6 months) and 18 witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
118
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(129 citation statements)
references
References 97 publications
10
118
1
Order By: Relevance
“…This finding is unexpected, as previous studies reported reduced FA in dyslexia and positive correlations with reading measures (Beaulieu et al, 2005;Deutsch et al, 2005;Lebel et al, 2013;Steinbrink et al, 2008). Recent tractography studies also showed lower FA in pre-reading children at family risk for dyslexia (Langer et al, 2017;Vanderauwera et al, 2017;Vandermosten et al, 2015;Wang et al, 2017), which is again not in line with our findings. These studies, however, relied on different age groups, tractography algorithms and tract quantification techniques, which makes a direct comparison with the current findings rather difficult.…”
Section: Discussioncontrasting
confidence: 94%
“…This finding is unexpected, as previous studies reported reduced FA in dyslexia and positive correlations with reading measures (Beaulieu et al, 2005;Deutsch et al, 2005;Lebel et al, 2013;Steinbrink et al, 2008). Recent tractography studies also showed lower FA in pre-reading children at family risk for dyslexia (Langer et al, 2017;Vanderauwera et al, 2017;Vandermosten et al, 2015;Wang et al, 2017), which is again not in line with our findings. These studies, however, relied on different age groups, tractography algorithms and tract quantification techniques, which makes a direct comparison with the current findings rather difficult.…”
Section: Discussioncontrasting
confidence: 94%
“…Deciphering amongst these possibilities cannot be achieved in observational and correlational studies, and is instead likely to require studies that are designed to directly manipulate the learning environment of the developing child (Keller and Just 2009; Webb et al 2015). Nevertheless, the present findings have important implications for prior developmental studies of pre-readers and early readers that have observed white matter differences in the context of identifying predictive biomarkers of reading impairments in samples of children with specific behavioral or familial risk factors for reading disorders (Saygin et al 2013; Myers et al 2014; Langer et al 2015; Vanderauwera et al 2015; Vandermosten et al 2015). Our findings show that differences in white matter structure can also be explained by whether children have acquired specific abilities for reading.…”
Section: Discussionmentioning
confidence: 78%
“…Here, we show that even at the onset of reading acquisition (and in contrast to Turkeltaub et al., ), reading skill correlates with the magnitude of word‐specific brain activation in the left vOT cortex, reinforcing the evidence that specialization for print in this region emerges with higher reading expertise. Although studies diverge on the concept of contribution of this area to nonreading tasks, they converge on an idea that it is generally involved in expert perception (Price & Devlin, ), including visual word processing (Langer et al., ). As predicted, literacy acquisition allows the left‐hemispheric spoken language network to be activated by print because correlation was also observed in language processing LH areas including inferior frontal, temporal and temporo‐parietal areas.…”
Section: Discussionmentioning
confidence: 99%